Classroom Innovation: A Study on the SPBL Model’s Role in Fostering Creative Thinking among Humanities Students - Nurul Itsnaini; Purwanto; Anang Dwi Ujianto (CV Bumi Spasial, 2024)
Indonesia's PISA results in 2018 have decreased due to the low ability of students to meet global demands. Creative thinking is one of the 21st-century skill competencies and the profile of Pancasila students. SPBL can improve students' creative thinking skills through its syntax. The purpose of this study was to determine the impact of integrating creative thinking teaching through spatial problem-based learning (SPBL). This quasi-experimental research design used a pretest and posttest control design with a sample of 66 students. The research instruments were in the form of tests and questionnaires. The essay test consists of five questions given at the pretest and posttest. The research data were analysed by independent sample t-test, which resulted in a significance value of 0.73 > 0.05. The gain score value of the experimental class (48%) was higher than the control class (40.1%). The results showed that the SPBL approach did not have a significant effect, but it could improve the creative thinking of class 11th IPS students at SMAN 1 Pronojiwo, Lumajang Regency. So, students must get used to the SPBL model.